Habitat monitoring reveals decreasing morlayer C:N ratios in Danish heathlands. (June 2018) - Strandberg, M.; Nielsen, K.E.; Damgaard, C.
Highlights: The C/N ratio of the morlayer of Danish heathland changes significantly within a 10-year time span. Both C and N increases in the morlayer despite management efforts to reduce N-load. There was not a significant relation between N deposition and increasing C/N ratio in the morlayer. Abstract: Danish heathlands constitute a large part of North Western European Atlantic heathland ecosystems, and their conservation status is of international importance. Modern agriculture has reduced the heathland area. Presently, heathlands are protected natural habitats, nevertheless, they are threatened by nitrogen (N) deposition despite efforts to reduce N emissions and increase nature management. A commonly used indicator of excess N in heathland habitats is the carbon:nitrogen ratio (C:N) in the morlayer, and using data from the Danish NATURA 2000 habitat monitoring program we show that the C:N ratio of coastal dwarf shrub heath was significantly reduced from 28 to 26 from 2004 to 2012, and in inland dry heathland from 27 to 22 from 2004 to 2014. In inland wet heathland, a non-significant reduction from 28 to 26 was observed from 2004 to 2012. These reductions in C:N ratio were mediated by significant increases of the concentration of C and N in the morlayer, and are likely to affect biodiversity in Danish heathlands. The rate of change in C:N ratio was not significantly related to model calculated N deposition.